2013
DOI: 10.1371/journal.pone.0053674
|View full text |Cite
|
Sign up to set email alerts
|

MRSA Nasal Carriage Patterns and the Subsequent Risk of Conversion between Patterns, Infection, and Death

Abstract: BackgroundPatterns of methicillin-resistant S. aureus (MRSA) nasal carriage over time and across the continuum of care settings are poorly characterized. Knowledge of prevalence rates and outcomes associated with MRSA nasal carriage patterns could help direct infection prevention strategies. The VA integrated health-care system and active surveillance program provides an opportunity to delineate nasal carriage patterns and associated outcomes of death, infection, and conversion in carriage.Methods/FindingsWe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…MRSA screening is routinely employed in many countries world-wide and is thought to be helpful in limiting MRSA spread. [156] However, in developing nations including India, universal active surveillance is expected to be resource and labor intensive and its benefits need to be appropriately weighed with respect to the outcomes obtained and its cost-effectiveness. Targeted surveillance may also be tested as a viable alternative in our settings, wherein the screening can be focused on patients who are more likely to convert to an MRSA colonized pattern, such as those in long-term care, greater than 70 years of age, having diabetes or antibiotic exposure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MRSA screening is routinely employed in many countries world-wide and is thought to be helpful in limiting MRSA spread. [156] However, in developing nations including India, universal active surveillance is expected to be resource and labor intensive and its benefits need to be appropriately weighed with respect to the outcomes obtained and its cost-effectiveness. Targeted surveillance may also be tested as a viable alternative in our settings, wherein the screening can be focused on patients who are more likely to convert to an MRSA colonized pattern, such as those in long-term care, greater than 70 years of age, having diabetes or antibiotic exposure.…”
mentioning
confidence: 99%
“…Targeted surveillance may also be tested as a viable alternative in our settings, wherein the screening can be focused on patients who are more likely to convert to an MRSA colonized pattern, such as those in long-term care, greater than 70 years of age, having diabetes or antibiotic exposure. [6]…”
mentioning
confidence: 99%
“…A retrospective cohort study reported that the MRSA infection rate was 14.4z in newly colonized patients in an intensive care unit (7). Another study utilizing a nasal PCR screening test for MRSA demonstrated that patients colonized with MRSA had an increased risk of infection and death, compared to non-colonized patients (8). Therefore, the prevention of MRSA colonization is important for preventing subsequent MRSA infections, and preventing this colonization can lead to decreased morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Different species of staphylococci are present in the nasal microbiome, principally Staphylococcus aureus and S. epidermidis (Frank et al, 2010). The nasal mucosa is known for its carriage of the methicillin-resistant S. aureus (Gupta et al, 2013). Although S. aureus can act as commensal in the healthy nasal microbiome, some virulent strains can grow at higher rates and affect the community structure, diminishing the abundance of the commensals Propionibacterium acnes and S. epidermidis (Frank et al, 2010).…”
Section: The Airway Microbiomementioning
confidence: 99%